NANOTUBS INCREASE TETRACHLOROMETHANE INDUCED OXIDATIVE STRESS - Letniak, N. Ya.; Kuzmak, I. P.; Korda, M. M. (International Journal of Medicine and Medical Research, 2017)
Background. The unique physical and chemical properties of carbon nanotubes determine wide-ranging prospects for their use in biology and medicine. The capability of nanotubes to transport medicines and chemicals inside a cell makes the possibility of classical toxicants toxicity increase in case of their intake to the body with nanotubes, an urgent issue. Objective. The aim of the research was to study the effect of carbon nanotubes on the capability of the chemical toxicant tetrachloromethane (TCM) to induce oxidative stress in serum and liver of rats. Methods. The experiments were performed on outbred male rats, which were administered intraperitoneally with 0.5 ml of suspension of single-walled, multi-walled or multi-walled functionalized COOH nanotubes (60 mg/kg) only or together with TCM (2 ml/kg). The animals were taken out of the experiment in 3, 6 and 48 hours after the administration of the nanotubes and TCM. The activity of catalase, superoxide dismutase, the content of thiobarbituric acid reactive substances (TARS), reduced glutathione, ceruloplasmin and total antioxidant activity of serum were determined in serum and liver. Results. It was established that under the influence of multi-walled carbon nanotubes the studied parameters changed significantly. The administration of tetrachloromethane to rats caused significant changes in all indicators. Maximal changes in the rates were recorded in the group of animals that were administered with carbon nanotubes and tetrachloromethane togeather. In this case, a number of the studied parameters of blood and liver significantly changed compare to the similar indicators of the group of animals, which were administered with the chemical toxicant only. Conclusions. Carbon nanotubes increase the capability of the chemical toxicant tetrachloride to cause oxidative stress in liver and serum.